Simple signs - Wheeler, Cindy (New York : Viking, 1995)
Demonstrates through illustrations and brief text twenty-nine American Sign Language signs for words such as hello, cry, dog, and love.
Keywords: American Sign Language -- Juvenile literature; Sign language